Introduction to Pascal and structured design Turbo Pascal version. - Dale, Nell; Weems, Chip (Lexington, Massachusetts D. C. Heath and Company, 1988)
Cover Title page : Turbo Pascal
Keywords: Structured programming; Pascal (Computer program language); Turbo Pascal (Computer file)